Two-dimensional imidazolyl material for catalyzing CO2 reduction and preparation method of two-dimensional imidazolyl material
By preparing the two-dimensional imidazol-based material [Fe(pbi)(SCN)2], the problems of low thermal stability and catalytic yield of 2D MOFs photocatalysts in the prior art were solved, and high selectivity and high yield photocatalytic CO2 reduction was achieved, and the material cost was low, the synthesis was simple, and the environment was friendly.
Patent Information
- Application Number
- CN202510077071.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-17
AI Technical Summary
Although the photocatalyst prepared with 2D MOFs as a material in the prior art has high selectivity, its thermal stability and catalytic yield are low, and the raw material cost is high, the synthesis method is complex, and the environmental burden is large.
A two-dimensional imidazol-based material with a specific structure of [Fe(pbi)(SCN)2] is used. The material is prepared by a specific synthetic method, and its unique two-dimensional structure and high specific surface area are used to improve the selectivity and yield of photocatalytic CO2 reduction.
High selectivity and high yield photocatalytic CO2 reduction is achieved, and the material has good stability and low cost, simplifies the synthesis process, and reduces energy consumption and environmental burden.
Smart Images

Figure CN119899393A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of MOF materials, and in particular relates to a two-dimensional imidazole-based material for catalyzing CO2 reduction and a preparation method thereof. Background Art
[0002] Metal-Organic Frameworks (MOFs) are a class of porous crystalline materials formed by self-assembly of metal ions or clusters and organic ligands. Due to their high specific surface area, designable pore structure, diverse functionalization methods and excellent photoelectric properties, MOFs show great application potential in the field of photocatalysis, especially in the photocatalytic reduction of carbon dioxide.
[0003] The porous structure of MOFs provides easily accessible active sites for CO2 molecules, while its tunable electronic structure and band structure can be optimized by designing organic ligands and metal centers to improve the separation efficiency of photogenerated carriers and catalytic activity. In addition, the structural diversity of MOFs allows researchers to explore different catalytic mechanisms and improve the selectivity of CO2 reduction by synthesizing different types of MOFs.
[0004] Two-dimensional metal-organic frameworks (2D MOFs) are a class of materials with highly ordered two-dimensional structures, formed by self-assembly of metal ions or clusters with organic ligands. These materials show great potential for application in the field of photocatalysis due to their unique structural characteristics, such as large specific surface area, adjustable pore structure and electronic properties. Two-dimensional metal-organic frameworks (2D MOFs) show great potential in the field of photocatalysis due to their unique physical and chemical properties. 2D MOFs have high specific surface area, adjustable electronic structure and excellent light absorption properties, which make them ideal candidates for efficient photocatalysts. In photocatalysis, 2D MOFs can provide abundant active sites, promote the separation and migration of photogenerated carriers, and thus improve the catalytic efficiency.
[0005] Recent research progress has shown that the efficiency and selectivity of photocatalytic CO2 reduction can be significantly improved by controlling the spin state of metal sites in MOFs, integrating pore partitioning and opening metal sites, and constructing bimetallic or multimetallic MOFs. For example, some MOF materials can efficiently reduce CO2 to CO or other organic matter under visible light irradiation and show good stability.
[0006] In summary, MOFs, as a background technology for photocatalytic reduction of carbon dioxide, has become a research hotspot in this field due to its unique structure and tunable performance, and has shown broad application prospects in realizing CO2 resource utilization and mitigating the greenhouse effect. However, in the prior art, photocatalysts prepared using 2D MOFs as materials have high selectivity but low thermal stability and catalytic yield.
[0007] The defects of the existing technology also include the following three aspects. First, the raw material cost of the existing technology is high, usually requiring precious metal salts and complex organic ligands, which are difficult to synthesize and expensive. Second, the synthesis method is extremely complicated, usually requiring high temperature and high pressure reaction conditions, ultrasonic stripping and other steps, and even involving electrolytic equipment and electricity consumption. Finally, the waste treatment process of the existing technology will also increase the burden on the environment.
[0008] Therefore, there is an urgent need for a photocatalyst material that has high selectivity, good stability, extremely high catalytic yield, and low cost and low energy consumption. Summary of the invention
[0009] In order to solve the technical problem that the photocatalyst prepared with 2D MOFs as the material in the above-mentioned prior art has high selectivity but low stability and catalytic yield and high cost, the present invention provides a photocatalytic material with high selectivity for photoreduction of carbon dioxide. Using this material as a catalyst can effectively increase the yield of photocatalytic reduction of carbon dioxide.
[0010] The above technical objectives of the present invention are achieved through the following technical solutions:
[0011] A two-dimensional imidazole-based material for catalytic CO2 reduction, the single crystal structure molecular formula of the material is:
[0012] [Fe(pbi)(SCN)2] (hereinafter referred to as pbi-Fe); wherein pbi is 1,1′-(1,4-phenylene)bis(1H-imidazole); the material belongs to the orthorhombic system, The bond angle of N-Fe-N is in the range of 86.08(12)-179.57(13), and it is connected to metallic iron atoms through ligands and bridged to form a regular two-dimensional network structure. Compared with the existing technology, this two-dimensional network structure MOF can further improve the selectivity and yield of photocatalytic carbon dioxide reduction.
[0013] The second object of the present invention is to provide a method for preparing the above-mentioned two-dimensional imidazole-based material, which mainly comprises the following steps:
[0014] S1, dissolving dihalobenzene, imidazole, copper salt, carbonate and salicylaldehyde oxime in degassed acetonitrile and heating the mixture under N2 atmosphere, cooling the mixture after the reaction, adding dichloromethane for washing and filtering, then extracting the mixture with water and brine in turn, and finally drying the mixture with sulfate and rotary evaporating the mixture to obtain the organic ligand pbi;
[0015] S2. Add the PBI and potassium thiocyanate prepared in step S1 to the methanol solution and mix well to obtain a mixed solution. Then, place the mixed solution, the iron salt solution and the methanol aqueous solution in a reaction container in descending order of density, seal and let stand to obtain a two-dimensional imidazole-based material suitable for single crystal X-ray diffraction testing.
[0016] In the step S1, the molar ratio of dihalobenzene to imidazole, copper salt, carbonate and salicylaldehyde oxime is 1:
[0017] 1.5~3.5:0.03~0.10:2~5:0.04~0.40, the volume ratio of degassed acetonitrile to dichloromethane is 1:5.0~12.5; the volume ratio of degassed acetonitrile to water is 1:4.5~11.5; the volume ratio of degassed acetonitrile to brine is 1:3~8, wherein the concentration of brine is 1%~20%.
[0018] As a preferred embodiment of the present invention, the dihalobenzene in step S1 is 1,4-diiodobenzene or 1,4-dibromobenzene; the copper salt is one of cuprous iodide, cupric sulfate, and cuprous oxide; the carbonate is cesium carbonate or potassium carbonate; and the sulfate is magnesium sulfate or sodium sulfate.
[0019] As a preferred embodiment of the present invention, the reaction temperature in step S1 is 80-90° C., and the reaction time is 24 h to 72 h.
[0020] The molar concentration ratio of the mixed solution to the iron salt solution in step S2 is 1:0.15-0.3; the molar ratio of PBI to potassium thiocyanate in the mixed solution is 1:0.2-2; the volume ratio of the mixed solution to the methanol aqueous solution is 1:0.5-0.8, wherein the methanol aqueous solution is a 50.0%-66.7% methanol solution; and the sealed standing time is 3-30 days.
[0021] As a preferred embodiment of the present invention, the iron salt in step S2 is one of ferrous trifluoromethanesulfonate, ferrous perchlorate, ferrous chloride and ferrous tetrafluoroborate.
[0022] The third object of the present invention is to provide the use of the above-mentioned two-dimensional imidazole-based material as a photocatalyst in improving the photocatalytic reduction of carbon dioxide production. As a two-dimensional metal organic framework (2D MOFs), pbi-Fe shows great potential in the field of photocatalysis due to its ultra-thin thickness, large specific surface area and highly accessible active sites; the structural characteristics of these materials give them advantages in light absorption, charge separation and transport, thus performing well in applications such as photocatalytic reduction of carbon dioxide. The application potential of two-dimensional MOF materials in the field of artificial photosynthesis is mainly reflected in their ability to simulate the photocatalytic process in natural photosynthesis. By designing and optimizing the structure of two-dimensional MOF, efficient CO2 photoreduction can be achieved, which is crucial for the development of artificial photosynthesis systems. These systems are designed to use solar energy to convert CO2 into fuels and chemicals, which is an effective way to achieve the goal of carbon neutrality.
[0023] In summary, the characteristics of the two-dimensional imidazole-based material of the present invention in the efficient photoreduction of carbon dioxide make it have broad application prospects in the field of artificial photosynthesis and are expected to provide strong support for future sustainable energy technologies. Specifically, a catalytic system is constructed with pbi-Fe material as a catalyst, RuPS as a photosensitizer, and BIH as a sacrificial agent. In an acetonitrile aqueous solution saturated with carbon dioxide, under the irradiation of a 400nm xenon lamp, CO2 is selectively reduced to CO and H2O is reduced to generate H2.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] (1) Pbi-Fe materials have shown great potential in the field of photocatalysis due to their unique two-dimensional structure, high specific surface area and tunable electronic properties. In the process of photocatalytic CO2 conversion, this material can adsorb CO2 molecules more efficiently and promote the reduction reaction of CO2 through the separation and migration of photogenerated carriers, thereby converting CO2 into useful chemicals such as methanol, formic acid or carbon monoxide.
[0026] (2) As a late transition metal catalyst, pbi-Fe has the characteristics of high activity, easy selectivity, and controllable polymer properties. In particular, the stability of the heteroatoms in the functional groups is superior to that of early transition metal catalysts.
[0027] (3) Pbi-Fe is an iron-based catalyst with the advantages of low price, high quantum efficiency, tunable structure, good selectivity and stability, and exhibits excellent CO2 photocatalytic reduction performance.
[0028] (4) The pbi-Fe photocatalytic carbon dioxide reduction has a very high catalytic yield and catalytic selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 (a) is a schematic diagram of the 2D MOF assembly of the two-dimensional imidazole-based material of Example 1, Figure 1 (b) Two-dimensional network structure of two-dimensional imidazole-based materials. Figure 1 (c) The three-dimensional topological stacking structure of two-dimensional imidazole-based materials.
[0031] Figure 2 This is the Fourier infrared spectrum of the two-dimensional imidazole-based material in Example 1.
[0032] Figure 3 This is the X-ray powder diffraction of the two-dimensional imidazole-based material in Example 1.
[0033] Figure 4 This is the thermogravimetric curve of the two-dimensional imidazole-based material in Example 1.
[0034] Figure 5 This is the impedance curve of the two-dimensional imidazole-based material in Example 1.
[0035] Figure 6 This is the Mott-Schottky curve of the two-dimensional imidazole-based material in Example 1.
[0036] Figure 7 This is a parallel experiment on the catalysis of the two-dimensional imidazole-based material in Example 1.
[0037] Figure 8 This is a catalytic spot sampling experiment of the two-dimensional imidazole-based material in Example 1.
[0038] Fig. 9 Schematic diagram of the frontier orbitals of the two-dimensional imidazole-based material and Fe-πMOL in Example 1.
[0039] Fig.10 The temperature-dependent solid UV and Tauc diagrams of the two-dimensional imidazole-based material of Example 1. DETAILED DESCRIPTION
[0040] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, a catalytic material for efficient photoreduction of carbon dioxide and its preparation method and application, its specific implementation method, characteristics and effects are described in detail as follows. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0041] All chemical reagents used in the experiment were purchased from merchants without purification. They were from manufacturers such as Bidex Pharmaceuticals, Anage Chemicals, and McLean Biopharmaceuticals. Details are shown in Table 1; experimental instruments and models are shown in Table 2.
[0042] Table 1 Experimental reagents
[0043] Reagents Specification Manufacturer 1,4-Diiodobenzene Analytical grade Bid Pharmaceuticals 1,4-Dibromobenzene Analytical grade ANEJI CHEMICALS Imidazole Analytical grade ANEJI CHEMICALS Cuprous iodide Analytical grade Shanghai MacLean Biopharmaceutical Technology Co., Ltd. Copper sulfate Analytical grade ANEJI CHEMICALS Cuprous Oxide Analytical grade Anhui Zesheng Technology Co., Ltd. Cesium carbonate Analytical grade ANEJI CHEMICALS Potassium carbonate Analytical grade Shanghai Lingfeng Pharmaceutical Group Salicylaldehyde oxime Analytical grade San Chemical Technology Co., Ltd. Ferrous trifluoromethanesulfonate Chemically pure Shanghai Haohong Biopharmaceutical Technology Ferrous chloride Chemically pure Anhui Zesheng Technology Co., Ltd. Ferrous Perchlorate Chemically pure ANEJI CHEMICALS Ferrous tetrafluoroborate Chemically pure Anhui Zesheng Technology Co., Ltd. Sodium chloride Analytical grade Shanghai Lingfeng Pharmaceutical Group Sodium sulfate Analytical grade Shanghai Lingfeng Pharmaceutical Group Magnesium sulfate Analytical grade Shanghai Lingfeng Pharmaceutical Group Potassium thiocyanate Analytical grade Sinopharm Group Dichloromethane Analytical grade Sinopharm Group Acetonitrile Analytical grade Sinopharm Group Deionized water Analytical grade Laboratory procurement
[0044] Table 2 Experimental instruments
[0045]
[0046]
[0047] Example 1
[0048] The molecular formula of the single crystal structure of the two-dimensional imidazole-based material provided by the present invention is: [Fe(pbi)(SCN)2] (hereinafter referred to as pbi-Fe)
[0049] Table 3 Crystal parameters
[0050]
[0051] a GOF=[∑[w(F0 2 -Fc 2 ) 2 ] / (Nobs-Nparams)] 1 / 2 , based on the data withI>2σ(I).
[0052] b R1=∑||F0|-|Fc|| / ∑|F0|; wR2=[∑[w(F0 2 -Fc 2 ) 2 ] / ∑[w(F0 2 ) 2 ]] 1 / 2 .
[0053] The smallest asymmetric unit of the material consists of a metallic iron atom, two thiocyanates and a ligand pbi, and the coordination mode is 6-coordination. Figure 1 As shown in (a), the pbi ligand, metal atoms and auxiliary ligands self-assemble to form a two-dimensional structure. Figure 1 As shown in (b), it can be seen from the crystal structure diagram that the ligands and metal atoms are extended and arranged to form a two-dimensional network structure through coordination, such as Figure 1 As shown in (c), the three-dimensional topological stacking shows the regular stacking arrangement of rhombuses.
[0054] The Fe-N bond length of the material is 2.164-2.201, and the Fe-N bond angle centered on iron is in the range of 86.08(12)-179.57(13), see Table 3, α=90°, β=90°, γ=90°, pbi-Fe belongs to the orthorhombic crystal system, and the crystal shape has a certain regularity. In addition, its unique electronic structure is conducive to the diffusion and adsorption of photoreactive substances.
[0055] Example 2
[0056] Synthesis of Organic Ligand 1,1′-(1,4-phenylene)bis(1H-imidazole)(pbi)
[0057] 1,4-Diiodobenzene (3.50mmol, 1.1547g), imidazole (8.75mmol, 0.5959g), copper sulfate (0.18mmol, 0.0288g), potassium carbonate (10.50mmol, 1.4490g) and salicylaldehyde oxime (0.70mmol, 0.0960g) were dissolved in 8ml of degassed acetonitrile, and reacted at 85°C for 48h under N2 atmosphere. After the reaction, the mixture was cooled to room temperature, washed and filtered with dichloromethane (3×25ml), and extracted with water (3×20ml) and 1% brine (2×20ml) in turn. The organic phase was dried over magnesium sulfate and the product was obtained by rotary evaporation.
[0058] Synthesis of [Fe(pbi)(SCN)2]
[0059] Ligand PBI (0.02mmol, 0.0042g) and potassium thiocyanate (0.04mmol, 0.0039g) were added to methanol solution (2ml) and mixed to obtain a 0.03mmol / ml mixed solution (2ml). Subsequently, the mixed solution, 0.01mmol / ml ferrous trifluoromethanesulfonate aqueous solution (2ml) and methanol aqueous solution (1ml, wherein the methanol aqueous solution is 50% methanol solution) were placed in a reaction container from top to bottom in order of density from large to small, and the container was sealed and allowed to stand for about 3 days to obtain a two-dimensional imidazole-based material suitable for single crystal X-ray diffraction test with a yield of 70%.
[0060] Example 3
[0061] Synthesis of Organic Ligand 1,1′-(1,4-phenylene)bis(1H-imidazole)(pbi)
[0062] 1,4-Diiodobenzene (3.80mmol, 1.2500g), imidazole (5.70mmol, 0.3882g), cuprous iodide (0.114mmol, 0.0217g), cesium carbonate (7.60mmol, 2.4762g) and salicylaldehyde oxime (0.152mmol, 0.0208g) were dissolved in 4ml of degassed acetonitrile and reacted under N2 atmosphere at 80°C for 24h. The suspension was cooled and filtered, dichloromethane (2×25ml) was added, and the mixture was extracted with water (3×15ml) and 10% brine (2×15ml) in sequence. The organic phase was dried over magnesium sulfate and the product was obtained by rotary evaporation.
[0063] Synthesis of [Fe(pbi)(SCN)2]
[0064] Ligand PBI (0.02 mmol, 0.0042 g) and potassium thiocyanate (0.02 mmol, 0.0020 g) were added to methanol solution (6 ml) and mixed to obtain a 0.01 mmol / ml mixed solution (6 ml). Subsequently, the mixed solution, 0.0025 mmol / ml ferrous chloride aqueous solution (4 ml) and methanol aqueous solution (3 ml, wherein the methanol aqueous solution is 66.7% methanol solution) were placed in a reaction container from top to bottom in order of density from large to small, and the mixture was sealed and allowed to stand for about 15 days to obtain a two-dimensional imidazole-based material suitable for single crystal X-ray diffraction test with a yield of 80%.
[0065] Example 4
[0066] Synthesis of Organic Ligand 1,1′-(1,4-phenylene)bis(1H-imidazole)(pbi)
[0067] 1,4-Diiodobenzene (4.10mmol, 1.3526g), imidazole (14.35mmol, 0.9773g), cuprous oxide (0.41mmol, 0.0587g), potassium carbonate (20.50mmol, 2.8332g) and salicylaldehyde oxime (1.64mmol, 0.2249g) were dissolved in 10ml of degassed acetonitrile, reacted at 85°C for 72h under N2 atmosphere, cooled to room temperature, filtered the suspension, added with dichloromethane (4×20ml), washed with water (3×24ml) and 5% brine (2×24ml) in turn, dried the organic phase with sodium sulfate, and concentrated by evaporation to obtain the product.
[0068] Synthesis of [Fe(pbi)(SCN)2]
[0069] Ligand PBI (0.02 mmol, 0.0042 g) and potassium thiocyanate (0.004 mmol, 0.0004 g) were added to a methanol solution (4 ml) and mixed to obtain a 0.006 mmol / ml mixed solution (4 ml). Subsequently, the mixed solution, a 0.001 mmol / ml ferrous perchlorate aqueous solution (2 ml) and a methanol aqueous solution (2 ml, wherein the methanol aqueous solution is a 50% methanol solution) were placed in a reaction container from top to bottom in order of density from large to small, and the container was sealed and allowed to stand for about 30 days to obtain a two-dimensional imidazole-based material suitable for single crystal X-ray diffraction test with a yield of 75%.
[0070] Example 5
[0071] Synthesis of Organic Ligand 1,1′-(1,4-phenylene)bis(1H-imidazole)(pbi)
[0072] Dissolve 1,4-dibromobenzene (3.80mmol, 0.8968g), imidazole (9.50mmol, 0.6450g), copper sulfate (0.20mmol, 0.0320g), cesium carbonate (11.40mmol, 3.7000g) and salicylaldehyde oxime (0.80mmol, 0.1050g) in 10ml of degassed acetonitrile, react under N2 atmosphere at 90°C for 72h, cool and add dichloromethane (2×25ml), wash and filter, wash with water (3×15ml) and 5% brine (2×15ml) in turn, dry the organic phase with magnesium sulfate, and obtain the product by rotary evaporation.
[0073] Synthesis of [Fe(pbi)(SCN)2]
[0074] Ligand PBI (0.02 mmol, 0.0042 g) and potassium thiocyanate (0.04 mmol, 0.0039 g) were added to a methanol solution (2 ml) and mixed to obtain a 0.03 mmol / ml mixed solution (2 ml). Subsequently, the mixed solution, a 0.01 mmol / ml aqueous solution of ferrous tetrafluoroborate (2 ml) and a methanol aqueous solution (1.5 ml, wherein the methanol aqueous solution is a 60% methanol solution) were placed in a reaction vessel from top to bottom in order of density from large to small, and the vessel was sealed and allowed to stand for about 30 days to obtain a crystalline two-dimensional imidazole-based material suitable for single crystal X-ray diffraction test, with a yield of 70%.
[0075] Characterization test of two-dimensional imidazole-based materials in Example 1
[0076] 1. Fourier infrared test:
[0077] like Figure 2 As shown, at 4000-400cm -1 In the range of 2000-2200cm-1 In the range, it can be seen that the crystalline two-dimensional imidazole-based material contains SCN - There is a peak on the surface of the ligand, but there is no such peak on the ligand, which proves that the crystal is formed by the coordination of the ligand and the auxiliary ligand.
[0078] 2. Thermogravimetric test:
[0079] Weigh 3.00 mg of sample accurately and place it in an appropriate crucible to ensure that the sample is evenly distributed. Heat at RT-800℃ in N2 atmosphere at a heating rate of 10℃ / min and record the change of sample mass with temperature. At the end of the experiment, draw the TG curve and analyze the thermal behavior of the sample pbi-Fe.
[0080] The collapse process of crystalline pbi-Fe is divided into two steps, such as Figure 4 As shown in the figure, the crystal begins to collapse at 285°C with a mass loss of 61.94%, which is the decomposition and detachment of the organic ligand. The second collapse ends because the residual structure left after the first collapse is unstable, and further decomposition or reorganization occurs, eventually causing the MOF to completely lose its crystal structure.
[0081] 3. Crystal powder diffraction:
[0082] The XRD experimental values were recorded on a RINT-2000 vertical goniometer with Cu Kα (40KV, 100mA) as the radiation source. The single crystal cif file was opened in Crystal Diffract and the PXRD pattern shown in the figure was obtained by calculation and simulation. Figure 3 As shown, it can be seen that the diffraction peak of pbi-Fe is basically consistent with the simulated peak of single crystal diffraction, which proves that the crystal purity is good.
[0083] 4. Electrochemical test:
[0084] The three-electrode system was used for testing, with Ag / AgCl electrode as reference electrode, Pt electrode as counter electrode, and glassy carbon electrode as working electrode. Before the test, nitrogen was introduced into the electrolyte of 0.1M sodium sulfate solution for 30 minutes to remove oxygen in the electrolyte. In addition, 5 mg of catalyst was taken into a centrifuge tube, and a mixed solution of 150 μL ethanol, 75 μL deionized water and 25 μL Nafion was added. A uniform catalyst ink was prepared by ultrasonic treatment for 15 minutes, and then immersed on a glassy carbon electrode with a diameter of 0.4 cm, and dried under ultraviolet light to complete the electrode preparation process.
[0085] The impedance of the catalyst was measured on an electrochemical workstation. From the impedance curve of the PBI ligand, it can be seen that the electrode process is controlled by charge transfer and diffusion processes. In the entire frequency range, Figure 5As shown, its Nyquist diagram is composed of a semicircle in the high-frequency region and a straight line in the low-frequency region. The arc radius of the semicircle is relatively small, and the smaller charge transfer resistance and higher electron-hole separation efficiency mean that pbi-Fe has a better photocatalytic effect, which is confirmed by the actual results.
[0086] The Mott-Schottky properties of the catalyst were measured at frequencies of 1000 Hz, 1500 Hz, and 2000 Hz. Figure 6 As shown, through data processing, the flat band potential of pbi-Fe is -0.88V, from which the conduction band potential of the pbi ligand is deduced to be -0.66V. Under standard conditions, the electrochemical reaction potential difference of carbon dioxide reduction to carbon monoxide is -0.52V. The test potential is more negative than this point, indicating the feasibility of the catalyst in kinetically catalyzing carbon dioxide.
[0087] 5. Solid UV test:
[0088] We used a UV-visible spectrophotometer to collect the reflected light from the sample surface through an integrating sphere and projected it onto the detector to generate an electrical signal to obtain the spectrum curve of pbi-Fe. The band gap of pbi-Fe was obtained by the Tauc plot method to be 2.20 eV. Based on electrochemical tests, such as Fig. 9 As shown in the figure, the conduction band potential of pbi-Fe is -0.66V through data processing and analysis from the Mott-Schottky plot of pbi-Fe, from which the valence band position of pbi-Fe can be inferred to be 1.54V. The conduction band potential is obtained based on the previous flat band potential. Compared with the carbon dioxide reduction potential of carbon monoxide, this conduction band potential is more negative and can effectively carry out photocatalysis. Comparing the conditions of 298K and 453K, as shown in the figure, Fig.10 As shown in the figure, from the ultraviolet spectrum and band gap change of pbi-Fe, it is found that the absorption peaks at 298K and 453K are basically the same, the band gap of pbi-Fe at 298K is 2.20eV, and the band gap of pbi-Fe at 453K is 2.19eV, with a difference of only 0.01eV. It can be seen that pbi-Fe has good stability in the range of 298K-453K. Since Fe-πMOL is obtained by ultrasonic exfoliation, the process requires high energy, which will cause disordered arrangement of the crystal structure; pbi-Fe can be obtained by direct preparation, and the preparation method is more stable than the existing technology.
[0089] Photocatalytic test (using the two-dimensional imidazole-based materials in Examples 1 to 5 as catalysts):
[0090] A 105W xenon lamp and a 400nm filter were used to simulate sunlight, and a catalytic tube was placed in a glass container filled with deionized water under the xenon lamp for irradiation. The photocatalytic products after irradiation were detected by gas chromatography. Figure 7As shown in Figure 2, through three parallel experiments, it can be obtained that under 5 h of light, the average CO production of pbi-Fe is 35.651 mmol / g. The sampling point experiment at 6 h draws the following conclusions: At 4 h, the catalytic reduction of carbon dioxide by pbi-Fe reaches a peak value, as shown in Figure 2. Figure 8 As shown, the CO production produced by pbi-Fe catalysis is as high as 36.504mmol / g, and the H2 production is 3.9573mmol / g. From this, it can be calculated that the selectivity for CO is as high as 90.22%. The CO production of 36.087mmol / g obtained by sampling 5h is compared with the parallel experiment of 35.651mmol / g. The relative error of the experiment is calculated to be 1.2%, which shows the reliability and accuracy of the experimental data. As shown in Table 4, compared with Fe-πMOL published in academic papers, this catalyst has a higher yield, which is 1.70 to 2.29 times higher than its yield, and the narrower band gap is conducive to the improvement of the photocatalytic effect.
[0091] Table 4 Catalytic effect evaluation table
[0092] catalyst Selection rate Yield Example 1 pbi-Fe 90.22% <![CDATA[9.126mmolg -1 h -1 ]]> Academic Journals Fe-πMOL 91.70% <![CDATA[3.980mmolg -1 h -1 ]]> Example 2 pbi-Fe 91.58% <![CDATA[8.653mmolg -1 h -1 ]]> Example 3 pbi-Fe 92.69% <![CDATA[7.961mmolg -1 h -1 ]]> Example 4 pbi-Fe 90.41% <![CDATA[7.218mmolg -1 h -1 ]]> Example 5 pbi-Fe 92.54% <![CDATA[6.761mmolg -1 h -1 ]]>
[0093] The excellent photocatalytic performance of pbi-Fe is inseparable from its unique structure. The imidazole group can enhance the charge separation efficiency of the photocatalyst by introducing a built-in electric field. The imidazole group can improve the catalytic stability of the photocatalyst. For example, in some photocatalysts, the presence of the imidazole group can improve the hydrophilicity of the material, thereby improving its catalytic stability. In addition, the imidazole group can improve its catalytic activity by changing the electronic structure of the photocatalyst, improving its light absorption capacity and the separation efficiency of photogenerated carriers. pbi-Fe is connected by 1,1′-(1,4-phenylene)bis(1H-imidazole) and metallic iron atoms through coordination, and continuously extends to form a regular two-dimensional network structure. The two-dimensional network structure of pbi-Fe has an ultra-thin thickness and a large specific surface area, which enables it to expose more active sites, thereby improving the catalytic efficiency; and the structure and function of the two-dimensional pbi-Fe can be achieved by designing the assembly between organic ligands and inorganic units to achieve different structural designs and customization, which provides the possibility for the optimization of photocatalytic performance.
[0094] In summary, the two-dimensional imidazole-based material of the present invention has good stability, extremely high catalytic yield and selectivity as a photocatalyst, while also taking into account low cost. Therefore, the two-dimensional imidazole-based material has a good reference value and good application prospects in catalyzing CO2 reduction.
[0095] The present invention is not limited by the above embodiments. The above embodiments and descriptions are only for explaining the principle of the present invention. Without departing from the spirit and scope of the present invention, the present invention may be subject to various changes and improvements, which are within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A two-dimensional imidazole-based material for catalytic CO2 reduction, characterized in that: The single crystal structure molecular formula of the two-dimensional imidazole-based material is: [Fe(pbi)(SCN)2], wherein pbi is 1,1′-(1,4-phenylene)bis(1H-imidazole).
2. A method for preparing the two-dimensional imidazole-based material according to claim 1, characterized in that: The preparation method comprises the following steps: S1, dissolving dihalobenzene, imidazole, copper salt, carbonate and salicylaldehyde oxime in degassed acetonitrile and heating the mixture under N2 atmosphere, cooling the mixture after the reaction, adding dichloromethane for washing and filtering, then extracting the mixture with water and brine in turn, and finally drying the mixture with sulfate and rotary evaporating the mixture to obtain the organic ligand pbi; S2. Add the PBI and potassium thiocyanate prepared in step S1 to the methanol solution and mix well to obtain a mixed solution. Then, place the mixed solution, the iron salt solution and the methanol aqueous solution in a reaction container in descending order of density, seal and let stand to obtain the target product.
3. The preparation method according to claim 2, characterized in that: In the step S1, the molar ratio of dihalobenzene to imidazole, copper salt, carbonate and salicylaldehyde oxime is 1:1.5-3.5:0.03-0.10:2-5:0.04-0.
40.
4. The preparation method according to claim 2, characterized in that: In step S1, the volume ratio of degassed acetonitrile to dichloromethane is 1:5.0-12.5; the volume ratio of degassed acetonitrile to water is 1:4.5-11.5; the volume ratio of degassed acetonitrile to brine is 1:3-8, wherein the concentration of brine is 1%-20%.
5. The preparation method according to claim 2, characterized in that: In step S1, the dihalogenated benzene is 1,4-diiodobenzene or 1,4-dibromobenzene; and the copper salt is one of cuprous iodide, cupric sulfate and cuprous oxide.
6. The preparation method according to claim 2, characterized in that: In step S1, the carbonate is cesium carbonate or potassium carbonate; the sulfate is magnesium sulfate or sodium sulfate.
7. The preparation method according to claim 2, characterized in that: In step S1, the reaction temperature is 80-90° C., and the reaction time is 24 h to 72 h.
8. The preparation method according to claim 2, characterized in that: The molar concentration ratio of the mixed solution to the iron salt solution in step S2 is 1:0.15-0.3; the molar ratio of PBI to potassium thiocyanate in the mixed solution is 1:0.2-2; the volume ratio of the mixed solution to the methanol aqueous solution is 1:0.5-0.8, wherein the methanol aqueous solution is a 50.0%-66.7% methanol solution; and the sealed standing time is 3-30 days.
9. The preparation method according to claim 2, characterized in that: The iron salt in step S2 is one of ferrous trifluoromethanesulfonate, ferrous perchlorate, ferrous chloride and ferrous tetrafluoroborate.
10. Use of the two-dimensional imidazole-based material according to claim 1 as a photocatalyst for increasing the yield of photocatalytic reduction of carbon dioxide.
Citation Information
Patent Citations
Nano-scale metal-organic framework material and preparation method thereof
CN110003489A
Material for efficiently adsorbing methyl orange and preparation method thereof
CN115353637A
Selective CO2 reduction spin catalytic material as well as preparation method and application thereof
CN115888826A
Catalytic material for efficiently photo-reducing carbon dioxide as well as preparation method and application of catalytic material
CN117447528A
Zirconium terephthalate-based metal organic framework with open metal sites
US20200353440A1
Cited By
Zn-tib-bdc crystal and preparation method and application thereof
CN122608904A